2016
DOI: 10.1021/jacs.6b04232
|View full text |Cite
|
Sign up to set email alerts
|

Singlet (Phosphino)phosphinidenes are Electrophilic

Abstract: A room-temperature stable (phosphino)-phosphinidene reacts with carbon monoxide, stable singlet carbenes, including the poor π-accepting imidazol-2-ylidene, and phosphines giving rise to the corresponding phosphaketene, phosphinidene-carbene and phosphinidene-phosphine adducts, respectively. Whereas the electronic ground-state calculations indicate a PP multiple bond character in which the terminal phosphorus is negatively charged, the observed reactivity clearly indicates that (phosphino)phosphinidenes are el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
1
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 60 publications
(41 reference statements)
6
96
1
12
Order By: Relevance
“…[48,49] Theu se of phosphaethynolate as source of P À has also been observed in the reaction between an unsaturated three-membered silicon ring (a cyclotrisilene) and Na(OCP) (Scheme 7). [48,49] Theu se of phosphaethynolate as source of P À has also been observed in the reaction between an unsaturated three-membered silicon ring (a cyclotrisilene) and Na(OCP) (Scheme 7).…”
Section: Angewandte Chemiementioning
confidence: 90%
See 1 more Smart Citation
“…[48,49] Theu se of phosphaethynolate as source of P À has also been observed in the reaction between an unsaturated three-membered silicon ring (a cyclotrisilene) and Na(OCP) (Scheme 7). [48,49] Theu se of phosphaethynolate as source of P À has also been observed in the reaction between an unsaturated three-membered silicon ring (a cyclotrisilene) and Na(OCP) (Scheme 7).…”
Section: Angewandte Chemiementioning
confidence: 90%
“…[66] Formally this reaction, which proceeds under loss of CO, can be viewed as a[3+ +1] cycloaddition of the P À anion to the P=C=Ounit. [48,49] [66] Note that this reaction does not proceed under substitution of CO by the isonitrile to give [P]ÀP=C= NR as observed with the bulky derivative with R = Ar**.…”
Section: Angewandte Chemiementioning
confidence: 96%
“…Its isolation opened a novel avenue towards NHC–phosphinidene adducts, simply by phosphinidene addition to carbenes. In this fashion, the phosphinidene adducts of CAAC 20 [ 20· P(DAP); δ 31 P = 76.3] and less electrophilic carbenes such as imidazol‐2‐ylidene 3 [ 3· P(DAP); δ 31 P = –68.2] and benzimidazol‐2‐ylidene 9 [ 9· P(DAP); δ 31 P = –35.5] have been prepared (Scheme ), illustrating the electrophilic nature of this phosphinidene …”
Section: Synthesis Of N‐heterocyclic Carbene–phosphinidene Adductsmentioning
confidence: 98%
“…While transition metal pnictides have been known since Schrock and Cummins described the first terminal phosphides in 1995, related examples for main group systems are still rare. Bertrand recently demonstrated that ligand bulk can indeed lead to the stabilisation of a terminal phosphorus atom bonded to a main group element centre in the form of a phosphino‐phosphinidene (Figure A) . The utilisation of a less bulky substituent set resulted in the formation of the phosphanyl‐diphosphene B .…”
Section: Figurementioning
confidence: 99%